Serum IgG levels to Epstein-Barr and measles viruses in patients with multiple sclerosis during natalizumab and interferon beta treatment - Clemens Warnke; Tomas Olsson; Ingrid Kockum; Tomas Bergström; Anna Fogdell-Hahn; Linn Persson Berg; Marcus Eriksson; Sonia Longhi; Elisabeth Thomsson; Malin Bäckström (BMJ Neurology Open, 2022)
Background Patients with multiple sclerosis (MS) demonstrate higher seroprevalence of Epstein-Barr virus (EBV) and increased anti-EBV IgG levels in serum compared with healthy controls. Intrathecal antibody production to measles virus (MeV) is a common finding in patients with MS.Objective To measure serum IgG reactivity to EBV glycoprotein 350 (gp350) and MeV nucleocapsid protein (NCORE) in patients with MS and healthy controls and to determine if reactivity changed in patients during interferon beta (IFNβ) and/or natalizumab (NAT) treatment. A secondary aim was to determine the seroprevalence of EBV in patients and controls.Methods Patients with MS (n=728) were included from the Swedish pharmacovigilance study for NAT. Paired serum samples from 714 patients drawn before and during NAT treatment and paired samples from 170 patients during prior IFNβ treatment were analysed. In total, 156 patients were included in both groups. Samples from 144 matched blood donors served as controls. Indirect ELISA was applied using recombinant EBVgp350 and MeV NCORE as antigens. EBVgp350 IgG seronegative samples were also analysed using EBV nuclear antigen 1 and viral capsid antigen (VCA).Results Patients with MS showed higher serum levels of anti-EBVgp350 and anti-MeV NCORE IgG compared with controls. During NAT treatment, the levels of anti-EBVgp350 and anti-MeV NCORE IgG declined, compared with the relatively stable levels noted during prior IFNβ treatment. Ten patients failed to demonstrate anti-EBVgp350 IgG but did show detectable anti-VCA IgG, indicating EBV seropositivity. In contrast, 10/144 controls were EBV seronegative.Conclusions Treatment with NAT, which is considered a selective immunosuppressive agent with a compartmentalised effect on the central nervous system, appeared to be associated with a moderate decrease in circulating IgG levels to EBVgp350 and MeV NCORE. All patients with MS were EBV IgG seropositive, supporting the potential role of EBV in the pathogenesis of MS.